The Extradition Agreement Between Indonesia and Australia: Case of Adrian Kiki Iriawan Extradition - Rumiyati, Rini (Fakultas Hukum Universitas Negeri Semarang, 2021)
Law is a tool to create justice and create peace of society. State money is something that must be accepted as a right for all Indonesian people, but many are misusing state money for their own benefit. Corruption is an extraordinary crime that harms the state, and hurts justice in society. Not only does it commit corruption, it is more sad that many corruptors are absent from the obligation to account for their actions. There are many ways by corruptors to escape the responsibility of prosecution, one of which is by fleeing to other countries. With the escape of the corruptor to another country, the country of origin experienced a huge loss. The first is because the person has caused material losses with a very large amount in which the money should be a right of the people of Indonesia, the second is to escape the corruptor to a foreign country of course this will hurt justice in the community because the corruptor can still live a comfortable life with the proceeds of the crime while many of the people who live in need. But what is wrong is still guilty and must get the punishment that should be in accordance with applicable regulations. It was not only the Indonesian people who condemned the Corruption Act, but the international community also began to pay attention to these actions. Extradition is an expression of the attention of the international community towards corruption. Extradition can be a solution in the event that the perpetrator escapes from his responsibility and runs away abroad, so that the person cannot be free from punishment. Adrian Kiki Iriawan is one of the Indonesian corruptors who escaped from his responsibilities and is hiding in a foreign country, he is a convict in the case of Bank Indonesia liquidity assistance, he used state funds amounting to 1.5 trillion for his own interests.